Monocyte Distribution Width as a Prognostic Biomarker of Mortality in Adult Patients with Sepsis or Severe Infection: A Systematic Review and Meta-Analysis - I Gusti Agung Made Risma Ari Pertiwi; I Komang Parwata (Sriwijaya Journal of Internal Medicine, 2026)
Background: Monocyte distribution width (MDW) is reported automatically with a routine complete blood count. Its diagnostic accuracy for sepsis has been meta-analysed repeatedly, but no synthesis has asked whether it predicts death once sepsis is present. Objective: To determine whether admission MDW predicts all-cause mortality in hospitalised adults with sepsis or severe infection. Methods: Three databases were searched for cohorts of hospitalised adults with sepsis or severe infection reporting admission MDW against all-cause mortality. The standardised mean difference (Hedges' g) was derived through three tiers (group means, mortality-AUC conversion, and 2 × 2 tables) and pooled with a DerSimonian–Laird random-effects model; risk of bias used the QUIPS tool. Results: Twelve cohorts from eight countries were included (2,289 patients; 475 non-survivors). MDW was higher in non-survivors (pooled Hedges' g = 0.60, 95% CI 0.39 to 0.80; p < 0.001; I² = 50.8%), robust across all twelve leave-one-out models (0.56 to 0.64). Elevated MDW carried roughly five-fold higher odds of death (OR 4.68; k = 9), but discrimination was modest (pooled AUC 0.676; k = 8). The pooled OR fell from a crude 3.99 to 2.68 after severity adjustment. No small-study effects were detected (Egger p = 0.846); certainty was low. Conclusion: Admission MDW was consistently higher in adults with sepsis or severe infection who died. The association was moderate, not confined to COVID-19 and survived severity adjustment, but discrimination was insufficient for individual prognostication and no threshold is recommended; MDW is best regarded as an adjunct to established severity scores.